An Updated Collection of Sequence Barcoded Temperature-Sensitive Alleles of Yeast Essential Genes. Issue 9 (1st September 2015) - Kofoed, Megan; Milbury, Karissa L; Chiang, Jennifer H; Sinha, Sunita; Ben-Aroya, Shay; Giaever, Guri; Nislow, Corey; Hieter, Philip; Stirling, Peter C
Abstract: Systematic analyses of essential gene function using mutant collections in Saccharomyces cerevisiae have been conducted using collections of heterozygous diploids, promoter shut-off alleles, through alleles with destabilized mRNA, destabilized protein, or bearing mutations that lead to a temperature-sensitive (ts) phenotype. We previously described a method for construction of barcoded ts alleles in a systematic fashion. Here we report the completion of this collection of alleles covering 600 essential yeast genes. This resource covers a larger gene repertoire than previous collections and provides a complementary set of strains suitable for single gene and genomic analyses. We use deep sequencing to characterize the amino acid changes leading to the ts phenotype in half of the alleles. We also use high-throughput approaches to describe the relative ts behavior of the alleles. Finally, we demonstrate the experimental usefulness of the collection in a high-content, functional genomic screen for ts alleles that increase spontaneous P-body formation. By increasing the number of alleles and improving the annotation, this ts collection will serve as a community resource for probing new aspects of biology for essential yeast genes.